(untitled) (Journal of Applied Learning and Teaching, 2021)
With a shift to mass online learning, maintaining the benefits of traditional on-campus collaborative group work is crucial for positive learning outcomes. Observations of online classes at a higher education business college reveal the risk of slipping into online lecturing if an educator feels that online group work ’doesn’t work’. This EdTech review explores Google’s suite of cloud-based shared files: Docs, Sheets, and Slides, through which we can maintain quality, efficient, and effective online group work. This review presents the history of cloud-based shared files, explores Google’s suite of products, discusses the importance of social constructivist online peer-peer learning, and concludes with practical shared file case studies. This review challenges the educator to be student-centred. It equips them with practical instructions to incorporate shared files into their classroom activities. It asks the educator to consider our commitment to the modern online student – to provide quality learning outcomes by implementing cloud-based shared files that improve collaborative online learning experiences.